Isolation, Characterization of Pyraclostrobin Derived from Soil Actinomycete Streptomyces sp. HSN-01 and Its Antimicrobial and Anticancer Activity - Halaswamy Hire Math; Sreenivasa Nayaka; Muthuraj Rudrappa; Raju Suresh Kumar; Abdulrahman I. Almansour; Karthikeyan Perumal; Girish Babu Kantli (MDPI AG, 2023)
The present study demonstrated the isolation, characterization, and antimicrobial and anticancer activity of active metabolite produced from mining-soil-derived actinomycetes. Among the 21 actinomycete isolates, the isolate HSN-01 exhibited significant antimicrobial activity in primary screening and was identified as Streptomyces sp. through 16S rRNA gene sequencing. The active metabolite was separated, purified, and confirmed through UV-Vis spectroscopy, FTIR, HR-ESI-MS, and NMR analysis and identified as pyraclostrobin. Further, the active metabolite pyraclostrobin was tested for antimicrobial and anticancer activity against the hepatocellular carcinoma (HepG2) cell line. The metabolite exhibited maximum antimicrobial potential with 17.0, 13.33, 17.66, 15.66, 14.66, and 14.0 mm of inhibition against B. cereus, S. aureus, E. coli, P. aeruginosa, S. flexneri, and C. glabrata. The active metabolite exhibited dose-dependent anticancer potential against the hepatocellular carcinoma (HepG2) cell line with the IC50 56.76 µg/mL. This study suggests that Streptomyces sp. HSN-01 is an excellent source of active secondary metabolites with various biological activities.